Revealing intercultural and interfaith communication in Manado which has a thousand churches as a city of tolerance - Yanti Dwi Astuti; Mohammad Zamroni; Siantari Rihartono (Informasi, 2022)
Indonesia is prone to violence with religious motives that could threaten the integrity of the Republic of Indonesia. Various conflicts with cultural and religious motives not only cause loss of property, but also human life. This research tries to map the intercultural and religious communication model in the city of Manado by using the theory of intercultural communication and symbolic interaction. The research method used is descriptive qualitative with data collection techniques through FGD, in-depth interviews, observation and documentation. The results of the study found that the creation of harmony between religious communities is a sense of tolerance for the people of Manado City due to the existence of the Forum for Religious Harmony (FKUB), the Agency for Inter-Religious Cooperation (BKSAUA) and the Women's Forum for Inter-Religious Harmony (FWKAUA). The model of interaction and relations between Manado's religious communities is carried out equally, tolerantly and inclusively. In addition, there are forms of language symbols, religious symbols, budget support and strong Manado city government policies for religious forums and the young generation of various religions in the city of Manado as well as the active role of the mass media which helps maintain harmony between religious adherents is in Manado.